Proposta de um guia metodológico e software para quantificação qualitativa na avaliação efetiva do aprendizado em avas e ensino presencial - Silva, Mislene Dalila da (2016)
The present research is an alternative proposal to the traditional continuous assessment. The traditional assessment quantifies but does not qualify and does not guarantee that knowledge will be kept in the memory for a long time. Thus, traditionally the student is evaluated and, after some time, even weeks, if the student makes the same evaluation, fatally he will not have the same success rate. This statement can be easily observed in the medical residency tests. Medical residents are reassessed after two years of residence, failing to achieve 30% of the previous test result,.as shown in the notes On AREMG 2016 site.. This is a strong indication that the assessment process quantifies but does not qualify how much of the learning has been retained and will be memorized over time. Through the methodology of the Structured Knowledge Maps - MCE and the Exponential Method of Effective Exponential Storage in the Binary Base - MMEEBB it is possible to guarantee the effectiveness and memorization of what was learned, even after weeks or years, when using the Learning Reinforcement Interval - IRA and the MCE properly. This work aims to disseminate a guide on the Web which teaches how to evaluate a student quantitatively and qualitatively, as well as ensure how to perpetuate in the memory of the same learned knowledge. It also presents the development and implementation of software that allows students to identify what the student does not know, allowing a customized and focused didactic material to be created.. This work also aims to explain and teach how to ensure that the student at the end of a stage is always 100% successful if the evaluation results in success. Thus, a student who takes, for example, grade 7 in a total of 10 points, means that he knows 100% of 70% of the content. In addition, the work allows to discriminate the known 70% and the missing 30%. The methodology applied in the work in question has a relevant bibliographical purpose and approach, constituting also an exploratory and descriptive field research. The methods and procedures studied envision a better understanding of the applicability of the Structured Knowledge Map and the Exponential Method of Effective Memorization in the Binary Basis applied in evaluations, guaranteeing 100% apprehensibility in what has been learned and memory retention with skill and competence, which ones are guaranteed in the evaluation process).